Parking standards as a steering instrument in urban and mobility planning. How to make parking standards more sustainable. - Gies, Jürgen; Hertel, Martina; Tully, Susan (My University, 2021)
One of the fields of activities within Park4SUMP is parking standards. Parking standards are also known as parking requirements or parking norms. This paper focuses on parking standards for new developments. New development is a broad term. It refers to new residential areas, but also to areas with mixed use of residential and commercial space, which is increasingly the focus of new urban expansion projects. Parking standards for purely commercial areas will not be considered in this paper.
Keywords: Stellplatzbedarf; Parkraumbedarf; Ruhender Verkehr; Parkraummanagement; Parkraumkonzept; Steuerungsinstrument; Stadtverkehrsplanung; Nachhaltige Verkehrsentwicklung; Beispielsammlung